If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(3x + 1) = -2X + 5 Reorder the terms: 2 + -1(1 + 3x) = -2X + 5 2 + (1 * -1 + 3x * -1) = -2X + 5 2 + (-1 + -3x) = -2X + 5 Combine like terms: 2 + -1 = 1 1 + -3x = -2X + 5 Reorder the terms: 1 + -3x = 5 + -2X Solving 1 + -3x = 5 + -2X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 5 + -1 + -2X Combine like terms: 1 + -1 = 0 0 + -3x = 5 + -1 + -2X -3x = 5 + -1 + -2X Combine like terms: 5 + -1 = 4 -3x = 4 + -2X Divide each side by '-3'. x = -1.333333333 + 0.6666666667X Simplifying x = -1.333333333 + 0.6666666667X
| 4x+48=0 | | 7x=8-8x | | -6x-48=0 | | (x-1)(x-2)(x-4)(x-5)-54=0 | | (x-1)(x-2)(x-4)(x-5)-54= | | 3x-9x^2-84x=0 | | x(x+15)=-56 | | 7a+5=3a+33 | | a^2+b^2+c^2=0 | | a^2+b^2+c^2+3abc=4 | | 2-8y=2y-8 | | a^2+b^2+c^2+4abc=4 | | 12=6(4y+1)-2(7y+7) | | 35n/2n | | f(x)=2x+x^2+3(4x)+17*f(7) | | f(x)=2x+x^2+3(4x)+17*7 | | 8(5u-3)-4(7u+4)=32 | | 4.5x+7-9.5x=2 | | 7(7u-8)=5(u-9)+385 | | 6x-2x-1=5+9(-63) | | -5y^2-27+48y=0 | | 0.3x+15.5=x-7.74 | | -6(x+1)-8=-4(x-3) | | 2(2x-2.2)=9x-4.4 | | -0.2x+2.91=-0.4x+1.11 | | -5w-(7/3)=(1/3w)-(3/4) | | 4x(x)+25x=0 | | (3/5u)-(4/3)=(-6/5u)=3 | | x^4+sqrt(17)*x^2-17=0 | | 7x-6=8x-9 | | 25/36-2/5(-1/3) | | 5(x+1.01)=4x |